(untitled) (International Journal of Environmental Sciences, 2025)
The purpose of this study is to examine the general condition and learning environment of the teaching practice schools at the College of Education, Morigaon, through an ecological and institutional survey. The survey looks at how institutional, social, and physical elements interact to influence the teaching-learning process. The results emphasise how crucial a supportive school environment is for encouraging good teaching methods and advancing the overall development of student teachers. Enhancing the calibre of teaching practice experiences, the study also emphasises the significance of teaching practices in teacher education.